Assessing the state of marine biodiversity in the Northeast Atlantic - McQuatters-Gollop, A.; Guérin, L.; Arroyo, N. L.; Aubert, A.; Artigas, L. F.; Bedford, J.; Corcoran, E.; Dierschke, V.; Elliott, S. A. M.; Geelhoed, S. C. V.; Gilles, Anita; González-Irusta, J. M.; et al. (Ecological Indicators, 2022)
The Northeast Atlantic, a highly productive maritime area, has been exposed to a wide range of direct human pressures, such as fishing, shipping, coastal development, pollution, and non-indigenous species (NIS) introductions, in addition to anthropogenically-driven global climate change. Nonetheless, this regional sea supports a high diversity of species and habitats, whose functioning provides a variety of ecosystem services, essential for human welfare. In 2017, OSPAR, the Northeast Atlantic Regional Seas Commission, delivered an assessment of marine biodiversity for the Northeast Atlantic. This assessment examined biodiversity indicators separately to identify changes in Northeast Atlantic biodiversity, but stopped short of determining the status of biodiversity for many species and habitats. Here, we expand on this work and for the first time, a semi-quantitative approach is applied to evaluate holistically the state of Northeast Atlantic marine biodiversity across marine food webs, from plankton to top predators, via fish, pelagic and benthic habitats, including xeno-biodiversity (i.e. NIS). Our analysis reveals widespread degradation in marine ecosystems and biodiversity, particularly for marine birds and coastal bottlenose dolphins, as well as for benthic habitats and fish in some regions. The poor biodiversity status of these ecosystem components is likely the result of cumulative effects of human activities, such as habitat destruction or disturbance, overexploitation, eutrophication, the introduction of NIS, and climate change. Bright spots are also revealed, such as recent signs of recovery in some fish and marine bird communities and recovery in harbour and grey seal populations and the condition of coastal benthic communities in some regions. The status of many indicators across all ecosystem components, but particularly for the novel pelagic habitats, food webs and NIS indicators, however, remains uncertain due to gaps in data, unclear pressure-state relationships, and the non-linear influence of ...